The Indigenous Identity of the South Saami Historical and Political Perspectives on a Minority within a Minority - Hermanstrand, Håkon; Kolberg, Asbjørn; Nilssen, Trond Risto; Sem, Leiv.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This open access book is a novel contribution in two ways: It is a multi-disciplinary examination of the indigenous South Saami people in Fennoscandia, a social and cultural group that often is overlooked as it is a minority within the Saami minority. Based on both historical material such as archaeological evidence, 20th century newspapers, and postcard motives as well as current sources such as ongoing land-right trials and recent works of historiography, the articles highlight the culture and living conditions of this indigenous group, mapping the negotiations of different identities through the interaction of Saami and non-Saami people through the ages. By illuminating this under-researched field, the volume also enriches the more general debate on global indigenous history, and sheds light on the construction of a Scandinavian identity and the limits of the welfare state and the myth of heterogeneity and equality.
Part I: Introduction -- Theoretical and Methodological Perspectives; Håkon Hermanstrand, Asbjørn Kolberg, Trond Risto Nilssen, Leiv Sem -- Part II: Sociolinguistic Perspectives -- Southern Saami Language and Culture - Between Stigma and Pride, Tradition and Modernity; Brit Mæhlum -- "But they call us the Language Police!" Speaker and Ethnic Identifying Profiles in the Process of Revitalizing the South Saami Language, Culture and Ethnic Identity; Inger Johansen -- Part III: Historical and Archaelogical Perspectives -- Identification of the South Saami in the Norwegian 1801 Cencus. Why is the 1801 Census a Problematic Source? Håkon Hermanstrand -- The Meaning of Words and the Power of Silence; Erik Nordberg -- Part IV: Text and Representation -- Puncturing Parts of History's Blindness: South Saami and South Saami Culture in Early Picture Postcards; Cathrine Baglo -- The Indigenous Voice in Majority Media. South Saami Representations in Norwegian Regional Press 1880 - 1990; Asbjørn Kolberg -- Part V: Hegemony and Current Conflicts -- Out of Print. A Historiography of the South Saami in Regional and National Works of History; Leiv Sem -- South Saami Cultural Landscape Under Pressure; Trond Riston Nilssen.
Keywords: Germanic languages; Anthropological linguistics; Language policy; Archaeology; Germanic Languages; Linguistic Anthropology; Language Policy and Planning; Archaeology